Common Sense as Political Struggle: Asserting the Right to Home Following the Grenfell Tower Fire. (December 2022) - Leaney, Sarah
The Grenfell Tower fire is a tragic manifestation of the brutality of the neoliberal conditionality of home. The systematic devaluing of the lives of residents in the social housing block is the result of stigmatisation-fuelled neglect. This article explores the ideological formation of the 'ideals' of home ownership, asserting a right to home as a means to resist the 'unequal distribution of precarity' that defines neoliberal formations of home.